PEMBELAJARAN FISIKA DENGAN MODEL LEARNING CYCLE 7E PADA MATERI LISTRIK DINAMIS UNTUK MENINGKATKAN PENALARAN FORMAL SISWA KELAS X SMA NEGERI 4 PEKANBARU - Nadia Darma Putri; M. Rahmad '; Nur Islami (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack: This research aims to describe and differentiate the student formal reasoning through the implementation of learning cycle 7E model for the material dynamic electricity in the class of X SMA Negeri 4 Pekanbaru. Population of this research is all of X classes with 304 students. Meanwhile the samples are 37 students in X3 as experimental class and 37 students in X4 as control class. The instrument of data collection in this study is a formal reasoning performance test which consists of 15 multiple choice items. Analysis of the data in this study was a descriptive analysis that was used to determine the performace of the physic learning through the criteria of absorption and effectiveness of learning. The inferential analysis was used to differentiate a formal reasoning considerably using independent sample t-test using SPSS 20 program. The analysis data shows: the average absorption of the class is 80.16% with the good category, and declared as an effective learning. The value of t tests is p = 0.008 means p < 0.05, then H0 is rejected. Which means that there are differences in formal reasoning test result between students in experiment class that taught using learning cycle 7E and control class that uses conventional learning with a level of 95%. It can therefore be concluded that the implementation of learning cycle 7E can be used as an alternative in the learning process in the classroom X SMA Negeri 4 Pekanbaru.Key Words: Learning cycle 7E, formal reasoning, dinamyc electricity